Toxic effects of titanium dioxide nanoparticles on reproduction in mammals - Minghui, Fan; Ran, Sun; Yuxue, Jiang; Minjia, Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium dioxide nanoparticles (nano-TiO2) are widely used in food, textiles, coatings and personal care products; however, they cause environmental and health concerns. Nano-TiO2 can accumulate in the reproductive organs of mammals in different ways, affect the development of the ovum and sperm, damage reproductive organs and harm the growth and development of offspring. The oxidative stress response in germ cells, irregular cell apoptosis, inflammation, genotoxicity and hormone synthesis disorder are the main mechanisms of nano-TiO2 toxicity. Possible measures to reduce the harmful effects of nano-TiO2 on humans and nontarget organisms have emerged as an underexplored topic requiring further investigation.